2019
DOI: 10.1007/s00249-019-01367-2
|View full text |Cite
|
Sign up to set email alerts
|

Possible sensor applications of selected DNA–surfactant complexes

Abstract: Although much research has been performed on DNA complexes carrying long alkyl chains (C10, C16, and C18), there is no information about physicochemical characterization of synthesized composites with allyl imidazole-based ionic liquids and quaternary ammonium salts with n-butyl chains. Here, complexes were synthesized by ion-exchange reactions between sonicated DNA and three ionic liquids (ILs) formed from two imidazole-based compounds, 1-allyl-3-methylimidazolium bromide (Amim) or 1-butyl-3-methylimidazolium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…As shown, an absorption band at 3192 cm −1 due to the –OH stretching, and two absorption bands at 1150 cm −1 , 926 cm −1 due to the –Al-O stretching (a) were recorded. After the immobilization of aptamer (b), a band at 3390 cm −1 due to –NH 2 , a band at 2918 cm −1 , a band at 1119 cm −1 due to –PO 2 − , two bands at 1150 cm −1 and 926 cm −1 due to the –Al-O-Si stretching, a band at 1538 cm −1 due to the –C = O stretching, a band at 1313 cm −1 due to the –C-N stretching of amide III, stretching a band at 1277 cm −1 due to the –PO 2 − stretching, a band at 1047 cm −1 due to the –C-O-P bending, an absorption band at 792 cm −1 due to the = C-H bending appeared, indicating the aptamer probe was immobilized inside the membrane [55] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…As shown, an absorption band at 3192 cm −1 due to the –OH stretching, and two absorption bands at 1150 cm −1 , 926 cm −1 due to the –Al-O stretching (a) were recorded. After the immobilization of aptamer (b), a band at 3390 cm −1 due to –NH 2 , a band at 2918 cm −1 , a band at 1119 cm −1 due to –PO 2 − , two bands at 1150 cm −1 and 926 cm −1 due to the –Al-O-Si stretching, a band at 1538 cm −1 due to the –C = O stretching, a band at 1313 cm −1 due to the –C-N stretching of amide III, stretching a band at 1277 cm −1 due to the –PO 2 − stretching, a band at 1047 cm −1 due to the –C-O-P bending, an absorption band at 792 cm −1 due to the = C-H bending appeared, indicating the aptamer probe was immobilized inside the membrane [55] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…An absorption band at 3013 cm −1 due to the -NH2 stretching was observed. Additionally, an absorption band at 2622 cm −1 due to -CH stretching, an absorption band at 1609 cm −1 due to -C=C stretching, an absorption band at 1480 cm −1 due to in-plane vibration of nucleotide bases, an absorption band at 1333 cm −1 due to the -C-N stretching of nucleotide bases, an absorption band at 1221 cm −1 due to the -PO2 − stretching, an absorption band at 1163 cm −1 due to the -C-O stretching of aliphatic ether in deoxyribose, an absorption band at 965 cm −1 due to PO2 − bending, an absorption band at 890 cm −1 due to the deoxyribose ring vibration, and an absorption band at 710 cm −1 due to sugar-phosphate vibration are clearly seen [38]. The ATR results indicated that the aptamer probes were immobilized on the surface of the electrode.…”
Section: The Surface Characterization Of the Electrodesmentioning
confidence: 97%
“…The Yam group created DNA hydrogels by the electrostatic attraction between phosphate groups and platinum ions [31] . As another positively charged molecule, cationic surfactants not only interact with phosphate groups to form hybrid hydrogels but also introduce their self‐assembly behaviors into the gelation process, leading to hydrogels with specific morphology such as spheres [32, 33] …”
Section: The Construction Of Dna‐based Networkmentioning
confidence: 99%